Studi Eksperimental: Perilaku Siklik Anticompression Split-K Braced Steel Frame - Oksa Eberly; Sri Murni Dewi; Wisnumurti Wisnumurti (Rekayasa Sipil, 2020)
This paper presents an experimental study on the behaviour of a braced steel frame with a proposed system: anticompression brace system (ABS) subjected to cyclic lateral loads. The ABS is proposed to deal with common brace buckling problems. In the study, split-K braced steel frames: with ABS and with ordinary brace system (OBS) were used as speciments. Cyclic loading tests were conducted to evaluate the performance of the proposed system in preventing the brace to buckle and to obtain the behaviour of the frame with ABS compared to the frame with OBS under cyclic quasistatic loading. From the cyclic tests, it was observed that the proposed system worked in preventing the braces to buckle, hence, the aimed state, “buckling prevention” was achieved. The results of the study also show that the frame with ABS had a lower initial stiffness compared to the frame with OBS, nevertheless, after exceeding drift ratio of 0.85% based on raw data or 0.64% based on fitted-curves, the frame with ABS exhibited good behaviour through lower degradations in stiffness and cyclic strength relative to the frame with OBS that experienced sudden and greater degradations.